Oligomer Formation of Tau Protein Hyperphosphorylated in Cells - Tepper, Katharina (J Biol Chem, 2014)
Abnormal phosphorylation (“hyperphosphorylation”) and aggregation of Tau protein are hallmarks of Alzheimer disease and other tauopathies, but their causative connection is still a matter of debate. Tau with Alzheimer-like phosphorylation is also present in hibernating animals, mitosis, or during embryonic development, without leading to pathophysiology or neurodegeneration. Thus, the role of phosphorylation and the distinction between physiological and pathological phosphorylation needs to be further refined. So far, the systematic investigation of highly phosphorylated Tau was difficult because a reliable method of preparing reproducible quantities was not available. Here, we generated full-length Tau (2N4R) in Sf9 cells in a well defined phosphorylation state containing up to ∼20 phosphates as judged by mass spectrometry and Western blotting with phospho-specific antibodies. Despite the high concentration in living Sf9 cells (estimated ∼230 μm) and high phosphorylation, the protein was not aggregated. However, after purification, the highly phosphorylated protein readily formed oligomers, whereas fibrils were observed only rarely. Exposure of mature primary neuronal cultures to oligomeric phospho-Tau caused reduction of spine density on dendrites but did not change the overall cell viability.